2015
DOI: 10.1299/transjsme.14-00646
|View full text |Cite
|
Sign up to set email alerts
|

A study on operator allocation aiming at the skill improvement for cell production system

Abstract: The cell manufacturing system of a labor concentration type is still in the important position of the manufacturing industry at this stage. Since an operator's skill is greatly related to productivity in labor concentration type cell productions, the operator's effective training is important. On the other hand, when operators learn and acquire the multi-skill tasks, the level of difficulty in their mastery depends on the contents of target operations, so a sufficient plan for training is required. In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Here, capacity for work is expressed according to the task by "skill index" adapting a skill map [7]. When a job standard time of task k in the product j is STjk and practical operation time of the operator i is set to ETjki, the value of skill index sjki is calculated by equation (1).…”
Section: Skill Indexmentioning
confidence: 99%
“…Here, capacity for work is expressed according to the task by "skill index" adapting a skill map [7]. When a job standard time of task k in the product j is STjk and practical operation time of the operator i is set to ETjki, the value of skill index sjki is calculated by equation (1).…”
Section: Skill Indexmentioning
confidence: 99%
“…Workspace configuration, task scheduling, and workers' education are investigated for a few workers in cell production. To schedule on-the-job training, Haraguchi et al [3] introduced a skill index and demonstrated that labor allocation based on this index efficiently improved the skill level of labors in computer simulations. Tanimizu et al [4] proposed two types of learning or familiarization, namely operational familiarization and knowledge familiarization, and demonstrated that the acquisition of knowledge during tasks shortens the assembly time effectively.…”
Section: Introductionmentioning
confidence: 99%